Bridging stress and satisfaction: a cognitive and theoretical approach using TTSC and Adlerian therapy - Mohd Kari, Dharatun Nissa Puad; Zulkifli Peter, Nurul Natasysa (Human Resource Management Academic Research Society, 2024)
Stress among university students has been increasing, especially in the post-pandemic period as students face various problems in adjusting to in-person learning settings. This research examines the correlation between stress, cognitive evaluation, and life satisfaction among first- and second-year students at a public university in Malaysia. This study employs the Transactional Theory of Stress and Coping (TTSC) and Adlerian Therapy as theoretical frameworks to elucidate the role of cognitive appraisal on students' perceptions of stress and its effects on their well-being. Data were gathered from 86 participants using validated instruments: The Perceived Stress Scale (PSS-10), Stress Appraisal Measure (SAM), and Satisfaction with Life Scale (SWLS). Research indicates that most students encounter modest levels of stress, cognitive evaluation, and life satisfaction. No significant correlation was seen between stress and life satisfaction; however, cognitive appraisal exhibited a positive correlation with life satisfaction, highlighting the significance of adaptive interpretations of stressors. A significant correlation between stress and cognitive appraisal was identified, indicating increased stress levels among students actively involved in assessment processes. These results highlight the need for treatments that enhance students' evaluation and coping mechanisms while cultivating purpose and connection to boost resilience and general wellbeing.